2007
DOI: 10.4049/jimmunol.179.10.7176
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ Produced by Human Papilloma Virus-18 E6-Specific CD4+ T Cells Predicts the Clinical Outcome after Surgery in Patients with High-Grade Cervical Lesions

Abstract: Cervical neoplastic lesions are associated with infection by high-risk human papilloma viruses (HPVs). HPV-16 and HPV-18 are the most common genotypes. It has been proposed that development of HPV-16-positive cervical lesions is associated with impaired CD4+ T cell immunity against early Ags. The aim of the study was to evaluate whether this impairment also applies to HPV-18. We investigated the presence and the quality of anti-HPV-18 E6 CD4+ T cell responses in the blood of 37 consecutive patients with high-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 28 publications
5
43
1
1
Order By: Relevance
“…For example, in vitro studies suggest that loss of episomal E2 with the emergence of integrated forms is associated with the endogenous activation of anti-viral genes, and therefore, the type-specific differences we have observed may be consistent with a recent report suggesting that HPV18 is more immunogenic than HPV16 (52,53).…”
Section: Discussionsupporting
confidence: 91%
“…For example, in vitro studies suggest that loss of episomal E2 with the emergence of integrated forms is associated with the endogenous activation of anti-viral genes, and therefore, the type-specific differences we have observed may be consistent with a recent report suggesting that HPV18 is more immunogenic than HPV16 (52,53).…”
Section: Discussionsupporting
confidence: 91%
“…The experiments were performed as described previously (31,44). Briefly, CD4 ϩ T cells were purified from total PBMC by using magnetic beads (Miltenyi Biotec) and cultured in 96-well plates at 3 ϫ 10 4 /well in five replicates for each condition in 200 l/well X-VIVO 15 (BioWhittaker) supplemented with penicillin (100 U/ml; BioWhittaker), streptomycin (50 mg/ml; BioWhittaker), and 3% heat-inactivated pooled human serum (tissue culture medium; BioWhittaker) in the presence of irradiated CD4 ϩ depleted PBMC as APC, at a CD4 ϩ :APC ratio of 1:3.…”
Section: Short-term Culture and Cytokine Release Assaymentioning
confidence: 99%
“…Normal donors and patients were tested for the presence of CD4 ϩ T cells against CEA sequences described to contain promiscuous and naturally processed epitopes (35, 37-39) using an ex vivo restimulation assay, which we previously demonstrated not to favor in vitro priming (44). CD4 ϩ T cells were cultured in several replicates in the presence or the absence of single CEA peptides or PHA as a positive control.…”
Section: Cd4mentioning
confidence: 99%
See 1 more Smart Citation
“…They observed that increasing levels of IL-4 and IL-10 levels were significantly associated with HPV infection and that decreasing levels of IL-2 and IFNwere associated with HPV status. Seresini et al (Seresini, Origoni et al 2007) measured lymphoproliferative responses and IL-2, IFN-g, IL-4, and IL-10 levels in PBMCs stimulated not with HPV16 peptides, but rather with HPV18-specific E6 peptides. Their analyses revealed that one or more HPV18 E6 peptides were able to induce a response in 40-50% of the women evaluated.…”
Section: Introductionmentioning
confidence: 99%